In Situ Architecting Endogenous Heterojunction of MoS2 Coupling with Mo2CTx MXenes for Optimized Li+ Storage. Issue 5 (13th December 2021) - Zhu, Shuang; Wang, Changda; Shou, Hongwei; Zhang, Pengjun; Wan, Ping; Guo, Xin; Yu, Zhen; Wang, Wenjie; Chen, Shuangming; Chu, Wangsheng; Song, Li
Abstract: Endogenous heterojunction of 2D MXenes with unique structure shows inspiring potential in energy applications, which is impeded by complex synthesis method and finite MAX materials. Herein, an in situ hydrothermal strategy is implemented to successfully synthesize unique endogenous hetero‐MXenes of amorphous MoS2 coupling with fluoride‐free Mo2 CT x (hetero‐Mo2 C) directly from Mo2 Ga2 C MAX. The distinctive morphology and heterojunction structure caused by the introduction of MoS2 endow the hetero‐MXenes with extraordinary structural stability and optimized Li + storage mechanism with improved charge transport and lithium ion adsorption capabilities. As a result, hetero‐Mo2 C exhibits excellent electrochemical performance with a high discharge specific capacity of 1242 mAh g ‐1 at 0.1 A g −1 and long cycle stability of 683.9 mAh g −1 after 1200 cycling. This work provides new insights into rational design of novel MXenes heterojunctions, practically important for the development of MXenes and their applications in high‐performance energy storage systems. Abstract : Unique endogenous hetero‐MXenes of amorphous MoS2 coupling with fluoride‐free Mo2 CT x directly from Mo2 Ga2 C MAX is constructed in situ. The obtained hetero‐Mo2 C shows extraordinary structural stability and optimized Li + storage mechanism with reversible structural transformation. Moreover, the improved capability of electron and ion transport endows hetero‐Mo2 C electrode with superior lithium storage performance, which surpasses all reported Mo2 C MXenes electrode materials.